Legal Issues in Sharia Pawn Gold Practice in Indonesia - Lastuti Abubakar; Tri Handayani (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
In the past few years, there is a trend of applying Islamic concept in Indonesia’s economic system, and it has implications for the existing legal system whereby new legal system should accommodate the changes. One of the institutions that use both conventional and shari’a system in Indonesia is pawning as an alternative financing mechanism, particularly for micro and consumption sectors. In practice, the function of pawning as a financing instrument has shifted into investment by continuously doing pawning and buying. As a result, people who need fund for financing are not facilitated.  The current regulation has allowed this practice for banks, pawn shops, and financial institutions to offer pawn gold that is not for financing activity but investment activity. Therefore, it raised a question whether this activity is complying with the shari’a principles. What kind of regulations that can make the function of pawning back to its original purpose as a financing mechanism. This study uses a normative juridical approach by using secondary data from the legal resources, with a specification of research methods using descriptive analysis whereas data are qualitatively described. The findings from this study reveal that the practice of pawning gold in Indonesia has not been fully consistent with the pawning function, therefore; it requires appropriate regulation so that the original function as the alternative financing for households and small, medium enterprises (SMEs) is not shifted to gold investment vehicles. Pawning gold is expected to be complementary to the businesses and households regarding financing that cannot be fulfilled by the banks and other financial institutions. Keywords: Pawn Gold, Legal Pawning, Shari’a